Просторово-типологічна структура угруповань мошок (Diptera: Simuliidae) басейну річки Тиси в межах Українських Карпат - Tepliuk, A. M.; Sukhomlin, K. B. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2018)
A total of 46 species of blackflies from 2 genera were recorded in the watercourses of the Tisa River basin within Ukrainian Carpathians. In qualitative terms, the genus Simulium Latreille, 1802 predominates, with 42 species in 5 subgenera: Nevermannia Enderlein, 1921 (9 species), Eusimulium Roubaud, 1906 (2 species), Wilhelmia Enderlein, 1921 (4 species), Obuchovia Rubtsov, 1947 (2 species) and Simulium Latreille, 1802 (25 species). The genus Prosimulium Roubaud, 1906 is represented with only 4 species. Moreover, 33 species develop in streams (the index of the species diversity of Simpson (Is) is 0,094), and 32 species (Is – 0,087) of Simuliidae develop in rivers. There are 19 common species for both types of watercourses (the index of similarity of Chekanovsky-Sorensen (I) is 0.37). Only 14 species of blackflies develop in streams, and only 13 species develop in rivers. Two dominant species (S. (s.str.) intermedium, S. (s.str.) trifasciatum) and 4 subdominant species (S. (s.str.) argyreatum, S. (s.str.) ornatum, S. (s.str.) reptans, S. (s.str.) variegatum) form the nucleus of the fauna Simuliidae of the Tisa River basin. The species diversity of blackflies reaches 33 species (Is – 0,075) at watercourses of the low mountain level (at altitudes up to 499 m), is has 38 species (Is – 0,067) at the middle mountain level (500–999 m) and only 24 species (Is – 0,021) at high mountain level (above 1000 m). Only 6 species (S. (Eusimulium) velutinum, S.(Obuchovia) brevifile, S. (s.str.) noelleri, S. (s.str.) rostratum, S. (s.str.) tuberosum and S. (s.str.) voilense) develop in the watercourses of the low mountain level, 5 blackfly species (S. (Nevermannia) codreanui, S. (Wilhelmia) pseudoequinum, S. (s.str.) argenteostriatum, S. (s.str.) paramorsitans and S. (s.str.) vulgare) develop in the watercourses of the middle mountain level and 2 species blackflies (S. (Nevermannia) crenobium and S. (Nevermannia) oligotuberculatum) develop in the watercourses of the high mountain level. There are 16 species of Simuliidae common for this high altitude belts, among them S. (Nevermannia) vernum, S. (s.str.) fontanum, S.(s.str.) intermedium, S.(s.str.) ornatum and S. (s.str.) trifasciatum did not reveal the definite patterns of belonging to the specific altitudes, since their quantity was approximately the same at different heights.